Analisis Gugatan Uni Eropa Terhadap Indonesia Dalam Larangan Ekspor Nikel di World Trade Organization - Syifa Febriani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to find out how the European Union's complaint against Indonesia regarding the ban on nickel exports at the World Trade Organization (WTO) occurred. The biggest problem with this is the degradation of nickel in nature. Solving this problem requires nickel empowerment. This can be avoided by stopping shipments abroad, which will help anticipate the current depletion of nickel supplies. Therefore, the Indonesian government must hurry to increase nickel supplies, with activities aimed at increasing the added value of nickel in the country's natural resources.